Applications of extreme value theory in finance. - Lim, Sharon Chin Wei. (2008)
This project attempts to model the extreme returns of different financial assets. The primary aim of this project is to attempt to fit extreme value distributions to daily returns for stock prices, currency exchange rates and commodity prices, namely STI, Yen/USD exchange rates and gold prices respectively. Our results show that extreme returns for the three assest, STI, YEN and gold, follow a Fr?chet distribution. Hence, we find that extreme value analysis is indeed a valuable tool in financial risk analysis.